Examining the effect of social media marketing dimensions on consumer attitudes and adoption among generation Y consumers - Keta, Keitumetse Tjama David (Vaal University of Technology, 2021)
It is evident that social media has become a fundamental instrument in society and has revolutionised the way society interacts and conducts business. More than 75 percent of the South African Generation Y population are active users of various social media platforms and the collective topics that are discussed include the status quo, entertainment, sports and other various issues that affect society as an integrated whole. However, many challenges are associated with social media concerning the affordability and accessibility of the internet. Consequently, it makes it a challenge for organisations to utilise social media as a reliable marketing instrument. Therefore, the study seeks to examine the effect of social media marketing dimensions on consumer attitudes and adoption among Generation Y consumers. The sample consisted of 285 self-reporting social media active users located in the Southern Gauteng region of South Africa. The study adhered to a quantitative approach and a snowball sampling method, whereby data were collected using a paper and pencil based self-administered questionnaire in 2019. A positivist research philosophy was followed whereby hypotheses where formulated for the study. In addition, formal procedure regarding research ethics were observed during empirical data collection and the questionnaire was also tested for reliability as well as validity. A pilot study preceded the main data collection survey processes. The collected data was analysed using descriptive statistics, correlation analysis and regression models. The results of the study indicated significant positive relationships for the three dimensions of social media marketing, namely in-formativeness (β= +0.302; t= 6.030; p<0.01), source credibility (β= +0.171; t= 2.767; p<0.01), perceived enjoyment (β=+0.169; t=2.956; p<0.00) and Generation Y consumer’s attitude. The fourth dimension being social identity, did not yield a statistically significant relationship in the regression model (β= 0.017; t= 0.256; p=0.01). Furthermore, significant positive relationships were also observed between consumer attitudes and the adoption of social media marketing (β= + 0.276; t-value= 4.841; p<0.01) among Generation Y consumers. As such, insight acquired from this study will assist both marketing academics as well as practitioners in comprehending Generation Y consumers’ perceptions on adoption and attitudes in relation to the adoption of social media as a marketing instrument. Based on the results, recommendations assert that, among others, marketing practitioners should effectively adopt social media as a marketing platform to communicate their marketing efforts and initiatives. Furthermore, marketers should integrate their marketing initiatives and strategies with the 4th industrial revolution. In addition, limitations, future research avenues are identified, and contributions of this study are discussed.
M. Tech. (Department of Marketing, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Social media; Social media marketing; Consumer attitudes; Adoption; Generation Y; Dissertations, Academic -- South Africa; Young adult consumers -- Attitudes; Generation Y -- Attitudes; Target marketing; Social media -- Economic aspects; Internet marketing; Consumer behavior